ANALISIS FAKTOR YANG BERHUBUNGAN DENGAN TINDAKAN EKSTERNAL VAGINAL DOUCING PADA WANITA USIA PRODUKTIF DENGAN PENDEKATAN TEORI HEALTH BELIEF MODEL DI DESA SUNGAI TUAN ULU KABUPATEN BANJAR - Rusdiana; Hj.Zubaidah; Raihana Norfitri (Jurnal Cakrawala Ilmiah, 2023)
Abnormal bleaching is often triggered by a woman's way of keeping herself clean, especially her genitals. External vaginal behavioral factors of douching in women of productive age with the Health Belief Model Approach (HBM), which describes preventive measures influenced by two assessments, namely the perceived threat of an individual's disease, the perception of vulnerability and the perceptions of the gravity and consideration of the benefits and disadvantages of taking such preventive action.The purpose of this study is to analyze the external vaginal douching behavioral factors in women of productive age with the Health Belief Theory Approach Model (HBM).The methodology of this research is to use correlational analytical research designs. The population in this study was a woman of fertile age who lived in Tuan Ulu River Village, Astambul district of Banjar Kalimantan South as many as 65 respondents with total sampling techniques. The perception of vulnerability has a significant influence on vaginal douching with a p-value value of 0.00 a. Perceptions of sensitivity have a significant impact on the practice of vaginal Douching with the p- value of 0.00.The perceptions of benefits have a meaningful influence upon the practices of vagonal douching at the p -value of 0,00.The percepts of obstacles have a significant influence over vaginal doching with an p - value of 0,00.